American marriage : a political institution - Yamin, Priscilla (American governance., 2012)
In American Marriage, Priscilla Yamin argues that marriage is a political institution to which actors turn either to stave off or to promote change over issues of race, gender, class, or sexuality. In the political struggle, certain marriages are pushed as necessary for the good of society, while others are contested or prevented.